Implementation of principle for responsible investment in distribution of bank credits on infrastructure projects - Nadia Andika; Lastuti Abubakar; Tri Handayani (Legality : Jurnal Ilmiah Hukum, 2021)
This research aims to discuss a large amount of credit lending is in line with the potential risk to the environment which is also caused by Toll Road construction activities. Therefore, Banks, Development, and the environment cannot be separated from one to another mainly because the Bank is responsible for taking preventive steps, other than implementing the substance of 5C principles, Bank is also obliged to implement several principles mentioned in POJK 51/2017, one of which is Principle for Responsible Investment. However, there are still no standards for the implementation of these principles or any strict penalties for Banks that are not applying the principle. This creates legal uncertainty, as it causes a potential risk that the Bank indirectly has not any obligation to implement it, yet only as a form of recommendation, whereas on the other hand, infrastructure development still damages the environment as it happened at the construction of Trans Sumatra Toll Road. In contrast to what Indonesia has done, Australia uses a variety of strategies to implement the Principle for Responsible Investment. In line with this issue, this research is using the normative legal research method where it is expected to provide different perspectives that will be useful for maximizing the realization of the Principles for Responsible Investment as part of Sustainable Finance in credit lending practices for Infrastructure development projects. Thus, it aims to make more detailed legal reforms, primarily regarding the standardization and sanctions of Principles for Responsible Investment including its derivative regulations hence that a sustainable environment will be realized.